Nutritional situation of children under five years of age in the city of Puerto La Cruz, Venezuela. - Ekmeiro-Salvador, Jesús E. (2023)
Introduction: for Venezuela, which is going through a profound political and socioeconomic situation, it is imperative to know the nutritional situation of the child population, in order to intervene on its possible consequences. Methods: to diagnose their anthropometric-nutritional situation, body weight, height and arm circumference were measured in 1717 infants from eight neighborhoods in the city of Puerto La Cruz, constructing the P/E, T/E, P/T and CBM indicators, using the WHO standards. Results: although most were within normal limits, a significant incidence of stunting (chronic malnutrition) followed by emaciation (acute malnutrition) was obtained, while overweight has practically disappeared. Conclusion: model consistent with the occurrence of prolonged forms of scarcity, which represents a great challenge for assistance, care and nutritional education programs. Keywords: malnutrition, infants, nutritional transition, communities, Venezuela.